In vitro efficacy of cypermethrin against Hyalomma anatolicum anatolicum - Prasad, L; Bagherwal, RK; Jayraw, AK; Rajput, N; Rajput, N; Shakya, M; Thankur, P (Indian Journal of Veterinary Sciences and Biotechnology, 2018)
The present investigation was undertaken to evaluate in vitro efficacy of cypermethrin against H. a.anatolicum. The engorged H. a.anatolicum females dropped on ground were collected from dairy farms of nearby villages of Mhow and were maintained in the laboratory till hatching of the eggs and larvae were used for further study. Larvae were placed in filter paper packets impregnated with 100, 200, 400, and 800 ppm concentrations of cypermethrin for 24 hours which revealed the per cent mortality 89.84, 93.70, 100 and 100%, while the corrected per cent mortality and efficacy was found 89.30, 93.36, 100 and 100% . the cause of development of resistance against Hyalomma anatolicum anatolicum has gained noticeable importance because of its role as the major vector of Theileria annulata in cattle. Use of acaricides is the most common method of tick control adopted by the cattle owners in India and these acaricides are applied on infested animals at frequent intervals. Indiscriminate use with incorrect concentrations of acaricides might be acaricides. Commonly used Cypermethrin (synthetic pyrethroid) is commercially available acaricide for tick control in India. Apart from its application against agriculturally important pests, it is also extensively used for the control of mosquitoes. The indiscriminate use of acaricides with incorrect concentrations of acaricides results in development of resistance against the a